Towards Regional Sustainability in Architecture - Raghad, Mourad (N/A, 2023)
ABSTRACT Today’s architecture is facing many challenges in terms of satisfying the escalating demand for sustainability solutions in order to preserve the earth’s resources for both the current and the coming generations. While most of the mentioned solutions are related to high-tech means, this research argues that traditional techniques are capable to offer sustainability solutions that match the ecological, social, and environmental requirements of the region. The objectives of this research are to develop a Sustainability Assessment Method that can be applied simply in testing building’s sustainability, through identifying the factors of sustainability that were available in the native architecture and to illustrate the importance of involving people in architecture, enhancing their participation in designing and constructing their own communities, and acknowledging the significance of their input especially in the schematic design, and construction phases. Studying the previous issues will pave the way to construct a criterion that can be applied for testing the sustainability, and achieving it through the different project’s implementation stages, without ignoring the region’s properties and identity. The research methodology has used descriptive, qualitative, and spatial analysis for two regional architecture examples, they were chosen in a way that one was categorized as a traditional architecture example, while the other was categorized as a contemporary architecture example. The two case studies were tested using the Proposed Sustainability Assessment Method in order to investigate the sustainability potentials in each of them. Discussing sustainability potential in the regional architecture, which is the main issue of this research, is an experiment to suggest some solutions for the current problems by investigating the validity of the traditional solutions which have proved their efficacy for many decades, and centuries. The thesis recommends a Proposed Environmental sustainability Checklist to be applied in the different stages of the project implementation, vi and it also concludes the importance of the local building materials especially when it is used alongside the traditional techniques to achieve the buildings’ sustainability, in addition to the importance of discussing the sustainability solutions in the early stages of the project’s design, and involving the local community in that stages accordingly. It was concluded that Sustainability Assessment Method represented an appropriate way to evaluate the sustainability performance of the buildings in the region. Formulation of sustainable assessment methods, environmental, social, and economical, requires the efforts of many experts and specialists in different aspects. The Proposed Sustainability Assessment Method is appropriate to be used for contemporary architecture in the region, yet it might need further input from different specialists. Thus, the research proposed further research to investigate issues that were beyond the limits of this research. The research suggests a number of recommendations for the designers, architects & local authorities, developers, and decision makers for achieving sustainability which is extracted from the region’s properties and identity. Keywords: Sustainability, traditional, regional, Vernacular, environment, assessment, local, construction, techniques.